Corncob Activated Carbon Adsorption Capacity (Zea mays L.) Against Rhodamine B. Dyes - Sudarmi (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
The aims of this experimental research are to determine the optimum of contact time, influence of stirring against absorbing power, and adsorption capacity of activated carbon corn cob to pigmen Rhodamin B. This research was done to vary contact time and first concentration of pigmen Rhodamin B. The result of this research showed that optimum of time contact needed activated carbon corn cob to adsorption pigmen Rhodamin B 45 minutes, rapid process way would be more biggest with more big the contact time until reach optimum time and adsorption capacity of activated carbon corn cob against pigmen Rhodamin B were 2,2255 mg/g. The value was more biggest than the adsorption capacity of activated carbon waste of sugar cane against pigment Rhodamin B were 2,078 mg/g. Isoterm system of the activated carbon corn cob to pigmen Rhodamin B followed isoterm system Langmuir with adsorption capacity were 2,2255 mg/g. Isoterm system Freundlich value of adsorption capacity were 1,481 mg/g.